High-resolution MCP-TimePix3 imaging/timing detector for antimatter physics - Glöggler, Lisa; Caravita, R.; Auzins, M.; Bergmann, B.; Brusa, R. S.; Burian, P.; Camper, A.; Castelli, F.; Cheinet, P.; Ciury\lo, R.; Comparat, D.; Consolati, G.; et al. (Measurement science and technology, 2022)
We present a hybrid imaging/timing detector for force sensitive inertial measurements designed for measurements on positronium, the metastable bound state of an electron and a positron, but also suitable for applications involving other low intensity, low energy beams of neutral (antimatter)-atoms, such as antihydrogen. The performance of the prototype detector was evaluated with a tunable low energy positron beam, resulting in a spatial resolution of 12 mm, a detection efficiency of up to 40% and a time-resolution in the order of tens of ns.
Gesehen am 25.09.2022